Detection of aerolysin and hemolysin genes in Aeromonas spp. isolated from environmental and shellfish sources by polymerase chain reaction - Yousr, A. H.; Napis, Suhaimi; Rahmat Ali, Gulam Rusul; Radu, Son (Universiti Putra Malaysia Press, 2007)
Polymerase chain reaction (PCR) technique was used to assay for the detection of specific genes in the genomes of the Aeromonas spp. isolated from environmental and shellfish sources, particularly aero and hlyA genes, responsible for aerolysin and hemolysin toxins production in this genus. The results showed that: (i) the 1500 bp amplicon of the hlyA gene was detected in 20/38 of the Aeromonas hydrophila, 13/38 of the A. caviae and 6/9 of the A. veronii biovar sobria isolates; (ii) the 690 bp amplicon of the aero gene was detected in 20/38 of A. hydrophila, 17/38 of A. caviae and 6/9 of A. veronii biovar sobria isolates; (iii) the nucleotide blast results of aerolysin gene sequences of the representative strains of A. hydrophila, A. caviae and A. veronii biovar sobria revealed a high homology of 94%, 95% and 95% with published sequences, respectively and; (iv) the protein blast showed 97%, 94% and 96% homology when compared to the published sequences, respectively. The finding of A. hydrophila virulence genes in other members of the genus Aeromonas, may give a new perspective to the significance of these results. The method described here may be a useful detection tool to assist in further investigation of aero and hlyA genes in the genus Aeromonas, especially for food microbiologist.